Based on the Results of Experimental Research of the Cellular Disc of a Mechanical Plant - G. U. Makhkamov (American Journal of Biodiversity, 2024)
This article presents the methodology and results of laboratory experiments on a mechanical seeder that sows onion seeds in rows